Sulfur-doped nickel-manganese layered double hydroxide electrode material, preparation method and capacitor

Through the synergistic action of sulfur doping and oxygen vacancies, a nickel-manganese layered double hydroxide electrode material with high specific capacitance and excellent magnification performance was prepared, which solved the problems of low conductivity and poor electron transport efficiency of existing electrode materials.

CN119446800BActive Publication Date: 2025-04-04XIAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510045730.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-04
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The existing transition metal layered double hydroxide electrode materials have low conductivity and poor electron transmission efficiency, resulting in unsatisfactory actual rate performance and cyclic stability.

Method used

Using a preparation method of sulfur-doped nickel-manganese layered dihydroxide electrode material, an electrode material with excellent electrochemical properties is formed by miscible metal salt, hexamethylenetetramine and thioacetamide in water, and then oxygen vacancies are introduced into the aqueous sodium borohydride solution.

Benefits of technology

The electrode material has a specific capacitance of 1110.13~1903.47F/g at a current density of 1A/g. When the current density increases from 1A/g to 20A/g, it still has a capacitance retention rate of 68.3%, and has excellent rate performance and cycling stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119446800B_ABST
    Figure CN119446800B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of capacitor electrode material preparation, and in particular to a sulfur-doped nickel-manganese layered double hydroxide electrode material, a preparation method and a capacitor. The preparation method uses a simple and easy one-step hydrothermal method to grow sulfur-doped nickel-manganese layered double hydroxide on nickel foam, and introduces oxygen vacancies on the electrode material by a safe and harmless chemical reduction method; wherein the layered double hydroxide has a large specific surface area and abundant active sites, which are conducive to the penetration of electrolytes and the diffusion of ions; the electronic structure of the electrode material can be synergistically optimized by combining sulfur doping with oxygen vacancies, and its adsorption capacity for electrolytes and electronic conductivity can be enhanced. The problem of low actual energy density and power density and poor cycle stability of transition metal layered double hydroxides existing in the prior art due to low electrical conductivity and poor electron transfer efficiency is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of capacitor electrode material preparation, specifically to a sulfur-doped nickel-manganese layered double hydroxide electrode material, a preparation method and a capacitor, and in particular to a sulfur-doped nickel-manganese layered double hydroxide electrode material containing oxygen vacancies, a preparation method and a capacitor. Background Art

[0002] With the rapid development of the world economy, energy crisis and environmental pollution have become the two most pressing problems in today's society. As a new type of energy storage device, supercapacitors have attracted widespread attention and research with their ultra-high power density, fast charge and discharge performance, and excellent cycle stability. They have broad application prospects in electric vehicles, mobile communication equipment, and energy management systems. For supercapacitors, the performance of electrode materials is crucial, which is directly related to the energy density and power density of supercapacitors. Therefore, researching and developing electrode materials with better performance has become a key way to improve the performance of supercapacitors.

[0003] The unique two-dimensional layered morphology of transition metal layered double hydroxides and the multiple valence states of transition metals enable transition metal layered double hydroxides to provide more redox active sites in electrochemical reactions, thereby storing more charge and achieving high capacitance performance. They are a type of pseudocapacitive electrode material for supercapacitors with high theoretical specific capacitance. However, the transition metal layered double hydroxide electrode materials currently prepared still have problems such as unsatisfactory actual rate performance and cycle stability due to low conductivity and poor electron transfer efficiency.

[0004] As an "intrinsic" method, defect engineering introduces defects by intentionally introducing or regulating during the material preparation or processing process. In particular, zero-dimensional point defects caused by vacancies and substitutions are very common in electrode materials. This changes the electronic structure of the material, and the defect-induced intermediate band gap electronic state promotes electrochemical charge transfer, thereby adjusting the conductivity of the material, improving the reaction kinetics, and obtaining excellent electrochemical performance. It is an effective way to solve the above problems.

[0005] Therefore, how to use defect engineering to adjust transition metal layered double hydroxide materials is the key to promoting their application and development in supercapacitors. Summary of the invention

[0006] In view of the problem that the transition metal layered double hydroxides in the prior art have low electrical conductivity and poor electron transfer efficiency, resulting in poor actual rate performance and cycle stability, the present invention provides a sulfur-doped nickel-manganese layered double hydroxide electrode material, a preparation method and a capacitor.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] The present invention provides a method for preparing a sulfur-doped nickel-manganese layered double hydroxide electrode material, comprising:

[0009] S1: placing a metal salt, hexamethylenetetramine and thioacetamide in water for mixing and dissolving to obtain a mixed solution; wherein the metal salt is a nickel salt and a manganese salt;

[0010] S2: immersing the nickel foam in the mixed solution to perform a hydrothermal reaction, and after the reaction is completed, washing and drying to obtain a nickel foam with sulfur-doped nickel-manganese layered double hydroxide;

[0011] S3: The nickel foam on which the sulfur-doped nickel-manganese layered double hydroxide is grown is immersed in a sodium borohydride aqueous solution for reaction. After the reaction is completed, the nickel foam is washed with water and dried to obtain a sulfur-doped nickel-manganese layered double hydroxide electrode material.

[0012] Optionally, the nickel salt is nickel chloride hydrate, nickel nitrate hydrate or nickel sulfate hydrate.

[0013] Optionally, the manganese salt is manganese chloride hydrate, manganese nitrate hydrate or manganese sulfate hydrate.

[0014] Optionally, in the mixed solution, the molar ratio of nickel salt, manganese salt and hexamethylenetetramine is (2-4):1:(1.25-2.5), and the concentration of the metal salt is 0.03-0.1 mol / L.

[0015] Optionally, the molar ratio of thioacetamide to metal salt is (0.05-0.1):1.

[0016] Optionally, the temperature of the hydrothermal reaction is 100° C. to 180° C., and the reaction time is 10 to 16 hours.

[0017] Optionally, the concentration of the sodium borohydride aqueous solution is 0.3-1 mol / L.

[0018] Optionally, in S3, the nickel foam having sulfur-doped nickel-manganese layered double hydroxide is immersed in a sodium borohydride aqueous solution at a reaction temperature of 0° C. to 30° C. and a reaction time of 0.5 to 1.5 h.

[0019] The present invention provides a sulfur-doped nickel-manganese layered double hydroxide electrode material prepared by the method. At a current density of 1 A / g, the specific capacitance of the sulfur-doped nickel-manganese layered double hydroxide electrode material is 1110.13-1903.47 F / g.

[0020] The present invention also provides a capacitor, comprising the above-mentioned sulfur-doped nickel-manganese layered double hydroxide electrode material.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The invention provides a method for preparing a sulfur-doped nickel-manganese layered double hydroxide electrode material. The method comprises the following steps: firstly, metal salt, hexamethylenetetramine and thioacetamide are mixed and dissolved in water to obtain a mixed solution; wherein the metal salt is a nickel salt and a manganese salt; then, nickel foam is immersed in the mixed solution to carry out a hydrothermal reaction, and after the reaction is completed, the nickel foam is washed with water and dried to obtain nickel foam with sulfur-doped nickel-manganese layered double hydroxide grown thereon; finally, the nickel foam with sulfur-doped nickel-manganese layered double hydroxide grown thereon is immersed in a sodium borohydride aqueous solution for reaction, and after the reaction is completed, the nickel foam is washed with water and dried to obtain the sulfur-doped nickel-manganese layered double hydroxide electrode material. The method uses a simple and easy one-step hydrothermal method to grow sulfur-doped nickel-manganese layered double hydroxide on nickel foam, and introduces oxygen vacancies on the electrode material through a safe and harmless chemical reduction method; wherein, the layered double hydroxide has a large specific surface area and abundant active sites, which is conducive to the penetration of electrolytes and the diffusion reaction kinetics of ions; sulfur doping can improve the wettability of the material and promote the reversible storage of metal ions, thereby enhancing the specific capacity and energy density of the battery; the introduction of oxygen vacancies can provide additional electronic states, increase the charge transfer efficiency, and further improve the conductivity and electrochemical reaction rate; the combination of sulfur doping and oxygen vacancies can synergistically optimize the electronic structure of the material, enhance its adsorption capacity and electronic conductivity for the electrolyte. In addition, the method uses nickel foam as the base material, which has a three-dimensional network structure and high porosity, providing good support for the growth of sulfur-doped nickel-manganese layered double hydroxide, helping to prevent the material from falling off and pulverizing during the charge and discharge process, and extending the service life of the electrode; at the same time, the porous structure of nickel foam is conducive to the penetration of electrolytes and the transmission of ions, further improving the electrochemical performance of electrode materials. This electrode material has a higher specific capacitance and can be widely used in supercapacitors and other high-performance batteries to meet the needs of modern energy storage devices for high efficiency and long life.

[0023] The nickel salt is nickel chloride hydrate, nickel nitrate hydrate or nickel sulfate hydrate. No toxic or harmful substances are produced during the preparation process, which meets environmental protection requirements. Nickel chloride, nickel nitrate and nickel sulfate are all common chemical raw materials with relatively low and stable market prices. By selecting these raw materials as the source of nickel salt, the preparation cost of electrode materials can be reduced.

[0024] The manganese salt is manganese chloride hydrate, manganese nitrate hydrate or manganese sulfate hydrate, and similarly no toxic or harmful substances are produced during the preparation process. At the same time, manganese resources are abundant, and manganese chloride, manganese nitrate and manganese sulfate are all common chemical raw materials with relatively low and stable market prices, which can reduce the preparation cost of electrode materials and further improve economic benefits.

[0025] In the mixed solution, the molar ratio of nickel salt, manganese salt and hexamethylenetetramine is (2-4):1:(1.25-2.5), and the concentration of metal salt is 0.03-0.1 mol / L, which helps to form a sulfur-doped nickel-manganese layered double hydroxide with uniform structure and stable crystal phase, which is beneficial to the rapid diffusion of ions and the effective transmission of electrons, thereby improving the electrochemical properties of the material.

[0026] The molar ratio of thioacetamide to metal salt is (0.05-0.1):1, which realizes precise control of the sulfur doping amount, and the sulfur atoms are introduced in situ during the preparation process, which can ensure the uniform distribution of sulfur atoms in the nickel-manganese layered double hydroxide.

[0027] The temperature of the hydrothermal reaction is 100° C. to 180° C., and the reaction time is 10 to 16 hours. Under the condition of 100° C. to 180° C., the hydrothermal reaction can be carried out at a moderate rate, which is conducive to the orderly growth and arrangement of crystals, and the formation of sulfur-doped nickel-manganese layered double hydroxides with uniform structure and stable crystal phase.

[0028] The concentration of the sodium borohydride aqueous solution is 0.3-1 mol / L, which is conducive to the introduction of oxygen vacancies. Appropriate oxygen vacancies combined with doped sulfur can effectively optimize the electronic structure of the material, improve the electrochemical activity, enhance its adsorption capacity for the electrolyte and electronic conductivity, achieve efficient electrochemical kinetics, and thus improve the electrochemical performance of the capacitor.

[0029] In the process of immersing the nickel foam with sulfur-doped nickel-manganese layered double hydroxide in a sodium borohydride aqueous solution to obtain the sulfur-doped nickel-manganese layered double hydroxide electrode material, the reaction temperature of immersing the nickel foam with sulfur-doped nickel-manganese layered double hydroxide in the sodium borohydride aqueous solution is 0° C. to 30° C., and the reaction time is 0.5 to 1.5 hours. The reaction conditions are relatively mild, which helps to reduce the generation of by-products and the degradation of materials and improve the stability of oxygen vacancy generation.

[0030] A sulfur-doped nickel-manganese layered double hydroxide electrode material prepared by the above method has a specific capacitance of 1110.13 to 1903.47 F / g at a current density of 1 A / g. When the current density increases from 1 A / g to 20 A / g, the electrode material still has a capacitance retention rate of 68.3%, and has excellent rate performance.

[0031] A capacitor includes the above-mentioned sulfur-doped nickel-manganese layered double hydroxide electrode material. Since the electrode of the capacitor uses the sulfur-doped nickel-manganese layered double hydroxide electrode material containing oxygen vacancies, it has significant advantages in electrochemical properties such as capacitance performance, cycle stability, safety, reliability and sustainability. These advantages make the capacitor have a wider application prospect and market competitiveness in the field of energy storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The present invention is a schematic diagram of a process for preparing a sulfur-doped nickel-manganese layered double hydroxide electrode material.

[0033] Figure 2 The present invention is a scanning electron microscope image and an element mapping image of the electrode materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention; wherein, a is a scanning electron microscope image of the electrode material NiMn-LDH@NF prepared in Comparative Example 1 at a magnification of 2000 times; b is a scanning electron microscope image of the electrode material NiMn-LDH@NF prepared in Comparative Example 1 at a magnification of 8000 times; c is a scanning electron microscope image of the electrode material NiMn-LDH@NF prepared in Comparative Example 1 at a magnification of 30000 times; d is a scanning electron microscope image of the electrode material S-NiMn-LDH@NF prepared in Comparative Example 2 at a magnification of 2000 times; e is a scanning electron microscope image of the electrode material S-NiMn-LDH@NF prepared in Comparative Example 2 at a magnification of 5000 times; f is a scanning electron microscope image of the electrode material S-NiMn-LDH@NF prepared in Comparative Example 2 at a magnification of 40000 times; g is a scanning electron microscope image of the electrode material S-NiMn-LDH-Ov prepared in Example 1 0.5 @ 1500 times magnified scanning electron microscope image of NF; h is the electrode material S-NiMn-LDH-Ov prepared in Example 1 0.5 @ NF magnified 5000 times scanning electron microscope image; i is the electrode material S-NiMn-LDH-Ov prepared in Example 1 0.5 @ 30000 times magnified scanning electron microscope image of NF; j is the electrode material S-NiMn-LDH-Ov prepared in Example 1 0.5 @Scanning electron microscope image of NF; k is the electrode material S-NiMn-LDH-Ov prepared in Example 1 0.5 @NF Mn element mapping; l is the electrode material S-NiMn-LDH-Ov prepared in Example 1 0.5 @S element mapping of NF; m is the electrode material S-NiMn-LDH-Ov prepared in Example 1 0.5 @Ni element mapping of NF; n is the electrode material S-NiMn-LDH-Ov prepared in Example 1 0.5 @NF's O element mapping diagram.

[0034] Figure 3 This is an X-ray photoelectron spectrum O1s diagram of the electrode materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.

[0035] Figure 4 The electrode material S-NiMn-LDH-Ov prepared in Example 1 of the present invention 0.5 @NF’s cyclic voltammetry test spectrum.

[0036] Figure 5 The electrode material S-NiMn-LDH-Ov prepared in Example 1 of the present invention 0.5 @NF’s constant current charge and discharge test spectrum.

[0037] Figure 6 The electrochemical performance test comparison diagram of the electrode materials prepared in Comparative Examples 1 to 5 of the present invention; wherein, a is a cyclic voltammetry curve comparison diagram; b is a constant current charge and discharge curve comparison diagram; c is a specific capacitance curve comparison diagram under different current densities; and d is an EIS curve comparison diagram under different current densities.

[0038] Figure 7 Comparative spectra of cyclic voltammetry tests of electrode materials prepared in Examples 1-4 of the present invention.

[0039] Figure 8 Comparative spectra of constant current charge and discharge tests of electrode materials prepared in Examples 1-4 of the present invention.

[0040] Fig. 9 Electrochemical impedance spectra of electrode materials prepared in Examples 1-4 of the present invention.

[0041] Fig.10 The cyclic voltammetry test comparison spectra of the electrode materials prepared in Example 1 and Comparative Examples 1-3 of the present invention are shown.

[0042] Fig.11 It is a comparative spectrum of constant current charge and discharge test of electrode materials prepared in Example 1 and Comparative Examples 1-3 of the present invention.

[0043] Fig.12 The electrochemical impedance spectra of the electrode materials prepared in Example 1 and Comparative Examples 1-3 of the present invention are shown.

[0044] Fig.13 The power-law relationship between peak current and scan rate, the relationship between capacitance contribution and scan rate, and the cycle performance test graph of the electrode material prepared in Example 1 of the present invention; wherein, a is a graph showing the power-law relationship between peak current and scan rate; b is a graph showing the relationship between capacitance contribution and scan rate; and c is a graph showing the cycle performance test. DETAILED DESCRIPTION

[0045] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0046] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0047] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0048] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0049] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0050] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0051] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0052] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0053] See also Figure 1 The present invention provides a method for preparing a sulfur-doped nickel-manganese layered double hydroxide electrode material, comprising:

[0054] S1: placing a metal salt, hexamethylenetetramine and thioacetamide in water and dissolving them to obtain a mixed solution; wherein the metal salt is a nickel salt and a manganese salt, specifically:

[0055] Dissolve nickel salt, manganese salt and hexamethylenetetramine in deionized water at a molar ratio of (2-4):1:(1.25-2.5) to make the concentration of metal salt 0.03-0.1 mol / L; then, add thioacetamide and stir evenly by magnetic stirring to obtain a mixed solution; wherein the nickel salt is nickel chloride hydrate, nickel nitrate hydrate or nickel sulfate hydrate; the manganese salt is manganese chloride hydrate, manganese nitrate hydrate or manganese sulfate hydrate; the molar ratio of thioacetamide to metal salt is (0.05-0.1):1. Preferably, the molar ratio of nickel salt, manganese salt and hexamethylenetetramine is 3:1:(1.25-2.5), more preferably 3:1:(1.25-2), and most preferably 3:1:1.25; the concentration of the metal salt is 0.04-0.1 mol / L, more preferably 0.05-0.08 mol / L, and most preferably 0.06-0.07 mol / L; the molar ratio of thioacetamide to metal salt is (0.05-0.10):1, more preferably (0.06-0.08):1, and most preferably (0.07-0.08):1.

[0056] S2: immersing the nickel foam in the mixed solution to perform a hydrothermal reaction, and after the reaction is completed, washing and drying are performed to obtain a nickel foam with sulfur-doped nickel-manganese layered double hydroxide grown thereon, specifically:

[0057] The mixed solution is transferred to a hydrothermal reaction kettle, and the nickel foam is immersed in the mixed solution, reacted at 100°C to 180°C for 10 to 16 hours, washed with water, and dried at 60°C to 80°C to obtain a nickel foam with sulfur-doped nickel-manganese layered double hydroxide. The temperature of the hydrothermal reaction is preferably 100°C to 150°C, more preferably 100°C to 130°C, and most preferably 110°C to 130°C.

[0058] S3: soaking the nickel foam on which the sulfur-doped nickel-manganese layered double hydroxide is grown in a sodium borohydride aqueous solution for reaction, and after the reaction is completed, washing and drying are performed to obtain a sulfur-doped nickel-manganese layered double hydroxide electrode material, specifically:

[0059] The nickel foam on which sulfur-doped nickel-manganese layered double hydroxide is grown is immersed in a sodium borohydride aqueous solution with a concentration of 0.3 to 1 mol / L, reacted for 0.5 to 1.5 hours at 0°C to 30°C, washed, and dried at 60°C to 80°C to obtain a sulfur-doped nickel-manganese layered double hydroxide electrode material; the concentration of the sodium borohydride aqueous solution is preferably 0.3 to 0.8 mol / L, more preferably 0.3 to 0.7 mol / L, and most preferably 0.3 to 0.5 mol / L; the reaction conditions are preferably 0°C to 20°C, more preferably 0°C to 10°C.

[0060] This method uses a simple and easy one-step hydrothermal method to grow sulfur-doped nickel-manganese layered double hydroxide on nickel foam, and introduces oxygen vacancies on the electrode material through a safe and harmless chemical reduction method; wherein, the layered double hydroxide has a large specific surface area and abundant active sites, which are conducive to the penetration of electrolytes and the diffusion of ions; sulfur doping can improve the wettability of the material and promote the reversible storage of metal ions, thereby enhancing the specific capacity and energy density of the battery; the introduction of oxygen vacancies can provide additional electronic states, increase the charge transfer efficiency, and further improve the conductivity and electrochemical reaction rate; the combination of sulfur doping and oxygen vacancies can synergistically optimize the electronic structure of the material, enhance its adsorption capacity for electrolytes and ionic conductivity, thereby improving the electrochemical performance of the capacitor.

[0061] A sulfur-doped nickel-manganese layered double hydroxide electrode material prepared by the above method has a specific capacitance of 1110.13 to 1903.47 F / g at a current density of 1 A / g. When the current density increases from 1 A / g to 20 A / g, the electrode material still has a capacitance retention rate of 68.3%, and has excellent rate performance.

[0062] A capacitor includes the above-mentioned sulfur-doped nickel-manganese layered double hydroxide electrode material. Since the electrode of the capacitor is a sulfur-doped nickel-manganese layered double hydroxide electrode material containing oxygen vacancies, it exhibits significant advantages in electrochemical properties such as capacitance performance, cycle stability, safety, reliability and sustainability. These advantages make the capacitor have a wider application prospect and market competitiveness in the field of energy storage.

[0063] Example 1

[0064] 3mmol nickel chloride hexahydrate, 1mmol manganese chloride tetrahydrate and 1.25mmol hexamethylenetetramine were dissolved in 60mL deionized water, and thioacetamide was added at a molar ratio of 0.075:1 to the metal salt, and stirred evenly by magnetic stirring for 1h to obtain a mixed solution. The obtained mixed solution was transferred to a hydrothermal reactor, and a nickel foam of 2cm×2cm was placed for hydrothermal reaction at a temperature of 120℃ for 12h. After the hydrothermal reaction was completed, the product was washed with deionized water and dried at 70℃ for 5h to obtain a nickel foam with sulfur-doped nickel-manganese layered double hydroxide. The obtained nickel foam with sulfur-doped nickel-manganese layered double hydroxide was soaked in a sodium borohydride aqueous solution with a concentration of 0.5mol / L, the reaction temperature was 0℃, the reaction time was 1h, and after the reaction was completed, it was dried at 70℃ for 5h to obtain a sulfur-doped nickel-manganese layered double hydroxide electrode material, named S-NiMn-LDH-Ov 0.5 @NF.

[0065] Example 2

[0066] 3mmol nickel chloride hexahydrate, 1mmol manganese chloride tetrahydrate and 1.25mmol hexamethylenetetramine were dissolved in 60mL deionized water, and thioacetamide with a molar ratio of 0.075:1 to the metal salt was added, and stirred evenly by magnetic stirring for 1h to obtain a mixed solution. The obtained mixed solution was transferred to a hydrothermal reactor, and a nickel foam of 2cm×2cm was placed for hydrothermal reaction. The temperature of the hydrothermal reaction was 120℃, and the hydrothermal reaction time was 12h. After the hydrothermal reaction was completed, the product was washed with deionized water and dried at 80℃ for 5h to obtain a nickel foam with sulfur-doped nickel-manganese layered double hydroxide. The obtained nickel foam with sulfur-doped nickel-manganese layered double hydroxide was soaked in a sodium borohydride aqueous solution with a concentration of 0.3mol / L, the reaction temperature was 0℃, the reaction time was 1h, and after the reaction was completed, it was dried at 80℃ for 5h to obtain a sulfur-doped nickel-manganese layered double hydroxide electrode material, named S-NiMn-LDH-Ov 0.3 @NF.

[0067] Example 3

[0068] 3mmol nickel chloride hexahydrate, 1mmol manganese chloride tetrahydrate and 1.25mmol hexamethylenetetramine were dissolved in 60mL deionized water, and thioacetamide with a molar ratio of 0.075:1 to the metal salt was added, and stirred evenly by magnetic stirring for 1h to obtain a mixed solution. The obtained mixed solution was transferred to a hydrothermal reactor, and a nickel foam with a size of 2cm×2cm was placed for hydrothermal reaction. The hydrothermal reaction temperature was 120℃ and the hydrothermal reaction time was 12h. After the hydrothermal reaction was completed, the product was washed with deionized water and dried at 70℃ for 6h to obtain a nickel foam with sulfur-doped nickel-manganese layered double hydroxide. The obtained nickel foam with sulfur-doped nickel-manganese layered double hydroxide was soaked in a 0.7mol / L sodium borohydride aqueous solution, the reaction temperature was 0℃, the reaction time was 1h, and after the reaction was completed, it was dried at 70℃ for 6h to obtain a sulfur-doped nickel-manganese layered double hydroxide electrode material, named S-NiMn-LDH-Ov 0.7 @NF.

[0069] Example 4

[0070] 3mmol nickel chloride hexahydrate, 1mmol manganese chloride tetrahydrate and 1.25mmol hexamethylenetetramine were dissolved in 60mL deionized water, and thioacetamide was added at a molar ratio of 0.075:1 to the metal salt, and stirred evenly by magnetic stirring for 1h to obtain a mixed solution. The obtained mixed solution was transferred to a hydrothermal reactor, and a nickel foam of 2cm×2cm was placed for hydrothermal reaction. The hydrothermal reaction temperature was 120℃ and the hydrothermal reaction time was 12h. After the hydrothermal reaction was completed, the product was washed with deionized water and dried at 60℃ for 8h to obtain a nickel foam with sulfur-doped nickel-manganese layered double hydroxide. The obtained nickel foam with sulfur-doped nickel-manganese layered double hydroxide was soaked in a sodium borohydride aqueous solution with a concentration of 1.0mol / L, the reaction temperature was 0℃, the reaction time was 1h, and after the reaction was completed, it was dried at 60℃ for 8h to obtain a sulfur-doped nickel-manganese layered double hydroxide electrode material, named S-NiMn-LDH-Ov 1.0 @NF.

[0071] Comparative Example 1

[0072] 3mmol nickel chloride hexahydrate, 1mmol manganese chloride tetrahydrate and 1.25mmol hexamethylenetetramine were dissolved in 60mL deionized water, stirred evenly by magnetic stirring for 1h to obtain a mixed solution. The obtained mixed solution was transferred to a hydrothermal reactor, and a nickel foam of 2cm×2cm was placed to perform a hydrothermal reaction at a temperature of 120℃ for 12h. After the hydrothermal reaction was completed, the product was washed with deionized water and dried at 70℃ for 5h to obtain an electrode material named NiMn-LDH@NF.

[0073] Comparative Example 2

[0074] 3mmol nickel chloride hexahydrate, 1mmol manganese chloride tetrahydrate and 1.25mmol hexamethylenetetramine were dissolved in 60mL deionized water, and thioacetamide was added at a molar ratio of 0.075:1 to the metal salt, and stirred evenly by magnetic stirring for 1h to obtain a mixed solution. The obtained mixed solution was transferred to a hydrothermal reactor, and a nickel foam of 2cm×2cm was placed to perform a hydrothermal reaction at a temperature of 120℃ and a hydrothermal reaction time of 12h. After the hydrothermal reaction was completed, the product was washed with deionized water and dried at 70℃ for 5h to obtain an electrode material named S-NiMn-LDH@NF.

[0075] Comparative Example 3

[0076] 3mmol nickel chloride hexahydrate, 1mmol manganese chloride tetrahydrate and 1.25mmol hexamethylenetetramine were dissolved in 60mL deionized water, stirred evenly by magnetic stirring for 1h to obtain a mixed solution. The obtained mixed solution was transferred to a hydrothermal reactor, and a nickel foam of 2cm×2cm was placed for hydrothermal reaction at a temperature of 120℃ for 12h. After the hydrothermal reaction was completed, the product was washed with deionized water and dried at 70℃ for 5h to obtain a nickel foam with nickel-manganese layered double hydroxide. The obtained nickel foam with nickel-manganese layered double hydroxide was soaked in a sodium borohydride aqueous solution with a concentration of 0.5mol / L, the reaction temperature was 0℃, the reaction time was 1h, and after the reaction was completed, it was dried at 70℃ for 5h to obtain an electrode material named NiMn-LDH-Ov@NF.

[0077] Comparative Example 4

[0078] 3mmol nickel chloride hexahydrate, 1mmol manganese chloride tetrahydrate and 1.25mmol hexamethylenetetramine were dissolved in 60mL deionized water, and thioacetamide was added at a molar ratio of 0.05:1 to the metal salt, and stirred evenly by magnetic stirring for 1h to obtain a mixed solution. The obtained mixed solution was transferred to a hydrothermal reactor, and a nickel foam of 2cm×2cm was placed to perform a hydrothermal reaction at a temperature of 120℃ for 12h. After the hydrothermal reaction was completed, the product was washed with deionized water and dried at 70℃ for 5h to obtain an electrode material named S 5 -NiMn-LDH@NF.

[0079] Comparative Example 5

[0080] 3mmol nickel chloride hexahydrate, 1mmol manganese chloride tetrahydrate and 1.25mmol hexamethylenetetramine were dissolved in 60mL deionized water, and thioacetamide was added at a molar ratio of 0.10:1 to the metal salt, and stirred evenly by magnetic stirring for 1h to obtain a mixed solution. The obtained mixed solution was transferred to a hydrothermal reactor, and a nickel foam of 2cm×2cm was placed to perform a hydrothermal reaction at a temperature of 120℃ for 12h. After the hydrothermal reaction was completed, the product was washed with deionized water and dried at 70℃ for 5h to obtain an electrode material named S 10 -NiMn-LDH@NF.

[0081] See also Figure 2 Electron microscope scanning tests were performed on the electrode materials prepared in Example 1, Comparative Example 1 and Comparative Example 2, respectively. The results showed that the nickel-manganese layered double hydroxide was uniformly loaded on the nickel foam in the form of a self-assembled hydrangea. The electrode materials subjected to in-situ sulfur doping and sodium borohydride chemical reduction treatment were all in the form of a self-assembled hydrangea, indicating that neither the in-situ sulfur doping nor the sodium borohydride chemical reduction treatment would destroy the morphology of the electrode material. This structure can ensure sufficient active sites and sufficient contact with the electrolyte, which is conducive to the electrochemical reaction. It can be seen from the element mapping diagram that the Ni, Mn, S and O elements are uniformly dispersed in the electrode material, indicating uniform doping of the sulfur element.

[0082] See also Figure 3 The electrode materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 were tested by X-ray photoelectron spectroscopy. The results showed that the oxygen defect ratio in S-NiMn-LDH@NF was greater than that in NiMn-LDH@NF, while the electrode materials prepared in Example 1, named S-NiMn-LDH-Ov 0.5 The sulfur-doped nickel-manganese layered double hydroxide electrode material of @NF has the most oxygen defects, indicating that sulfur doping will introduce a portion of oxygen vacancies, and sodium borohydride chemical reduction will further increase the concentration of oxygen vacancies, thereby improving the conductivity and electrochemical activity of the electrode.

[0083] The electrode materials prepared in the comparative example and the example were stirred and mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 16:3:1 in ethanol to form a uniform slurry, applied to a 1 cm×1 cm nickel foam, and used as a working electrode after drying. A platinum electrode and a saturated calomel electrode were used as an auxiliary electrode and a reference electrode, respectively, and 6 mol / L KOH was used as an electrolyte. The electrochemical performance under three electrodes was tested on a Coster electrochemical workstation.

[0084] See also Figure 4 , is the sulfur-doped nickel-manganese layered double hydroxide electrode material S-NiMn-LDH-Ov prepared in Example 1 0.5@NF's cyclic voltammetry (CV) curve at different scan rates shows a clear redox peak, proving its pseudocapacitive properties. As the scan rate increases, the CV curve can still maintain its original shape, indicating that the prepared electrode material has good electrochemical reversibility and fast charge and discharge capabilities.

[0085] See also Figure 5 The sulfur-doped nickel-manganese layered double hydroxide electrode material S-NiMn-LDH-Ov prepared in Example 1 0.5 @NF constant current charge and discharge (GCD, Galvanostatic Charge / Discharge Curve) curves at different current densities show that the GCD curves at different current densities are highly symmetrical, which shows that the prepared materials have excellent coulombic efficiency and excellent electrochemical reversibility. After calculation, the specific capacitance of the electrode material at current densities of 1A / g, 2A / g, 3A / g, 5A / g, 10A / g and 20A / g is 1903.47F / g, 1749.87F / g, 1668.40F / g, 1581.67F / g, 1454F / g and 1300F / g, respectively. It can be seen that even at a high current density of 20A / g, the material still has a capacitance retention rate of 68.3%, proving its excellent rate performance.

[0086] See also Figure 6 , Figures a to d are the CV curves of the electrode materials prepared in Comparative Examples 1, 2, 4 and 5 at a scan rate of 5mV / s, the constant current charge-discharge curves at a current density of 1A / g, the specific capacitance and EIS curves at different current densities. From Figure a, it can be seen that the CV curves of each electrode material show a pair of clear redox peaks, proving their typical pseudocapacitive properties. Compared with NiMn-LDH@NF, the redox peaks of the electrode materials become stronger after sulfur doping, among which the peak of S-NiMn-LDH@NF prepared in Comparative Example 2 is the strongest. The constant current charge-discharge curves in Figure b all show a highly symmetrical charge-discharge platform, which is consistent with the results of the CV curves, which shows that the prepared materials have excellent coulombic efficiency and excellent electrochemical reversibility, and the charge-discharge time of S-NiMn-LDH@NF is the longest, which is also consistent with the strongest redox peak result of the CV curve. Figure c is a comparison of specific capacitance at different current densities. It can be seen that at different current densities, S-NiMn-LDH@NF exhibits the highest specific capacitance. Figure d shows that S-NiMn-LDH@NF presents the smallest charge transfer resistance. Therefore, the best electrochemical performance of sulfur-doped NiMn-LDH@NF is prepared by selecting a molar ratio of 0.075:1 of thioacetamide to metal salt.

[0087] See also Figure 7, which is a comparison of the CV curves of the electrode materials prepared in Examples 1-4 and the comparative example at a scanning rate of 10 mV / s. It can be seen that all five electrode materials have clear redox peaks, proving their pseudocapacitive properties. Among them, the electrode material S-NiMn-LDH-Ov prepared in Example 1 0.5 @NF has the largest integrated area of ​​CV curve, indicating that the appropriate sulfur doping ratio and oxygen vacancy concentration can effectively improve the electrochemical performance of nickel-manganese layered double hydroxide.

[0088] See also Figure 8 , which is a comparison of the GCD curves of the electrode materials prepared in Examples 1-4 and the comparative example at a current density of 1A / g. The GCD curves of the five materials all have obvious charge and discharge platforms, among which the electrode material prepared in Example 1 has the longest charge and discharge time, which can further prove that the electrode material S-NiMn-LDH-Ov prepared in Example 1 0.5 @NF has a high specific capacitance. According to calculations, S-NiMn-LDH-Ov 0.5 @NF、NiMn-LDH-Ov 0.5 @NF、S-NiMn-LDH-Ov 0.3 @NF、S-NiMn-LDH-Ov 0.7 @NF and S-NiMn-LDH-Ov 1.0 The specific capacitances of @NF are 1903.47F / g, 1110.13F / g, 1796.93F / g, 1653.40F / g and 1188.73F / g, respectively, indicating that sulfur doping can promote the reversible storage of metal ions, enhance the specific capacity and energy density of the battery, and that changes in oxygen vacancy concentration can improve the electrochemical properties of nickel-manganese layered double hydroxide to varying degrees.

[0089] See also Fig. 9 , is a comparison of the electrochemical impedance spectra (EIS) of the electrode materials prepared in Examples 1-4 and the comparative example. In the low-frequency region, the slope of the image can clearly observe the ion transfer ability of the electrode material. The larger the slope, the greater the ion transfer ability. It can be seen that S-NiMn-LDH-Ov 0.5 @NF has a larger slope, proving its better performance. At the same time, due to the formation of a double electric layer between the electrode and the electrolyte, a small semicircle image appears in the high-frequency region. The diameter of the small semicircle represents the transfer resistance of the electrons. It can be observed that S-NiMn-LDH-Ov 0.5 @NF semicircle diameter is significantly smaller than that of other electrode materials, indicating that it has smaller electron transfer resistance and is more conducive to the rapid passage of electrons.

[0090] See also Fig.10From the comparative spectra of the cyclic voltammetry tests of the electrode materials prepared in Example 1 and Comparative Examples 1-3, it can be seen that the electrode materials prepared in Example 1 and Comparative Examples 1-3 all show a pair of redox peaks, showing typical pseudocapacitive behavior. Compared with Comparative Example 1, the redox peaks of Comparative Examples 2 and 3 are enhanced, indicating that both sulfur doping and oxygen vacancies can improve the electrochemical activity. Example 1 shows the highest redox peak, indicating that under the synergistic effect of sulfur doping and oxygen vacancies, the electrochemical performance is significantly improved.

[0091] See also Fig.11 , From the constant current charge and discharge test comparison spectra of the electrode materials prepared in Example 1 and Comparative Examples 1-3, it can be seen that the GCD curves of the electrode materials prepared in Example 1 and Comparative Examples 1-3 all have symmetrical charge and discharge platforms, which are consistent with the results of the cyclic voltammetry curves, indicating excellent pseudocapacitor performance, excellent coulombic efficiency and outstanding electrochemical reversibility. Compared with Comparative Example 1, the charge and discharge time of Comparative Examples 2 and 3 is longer, indicating that both sulfur doping and oxygen vacancies can improve the electrochemical activity. Example 1 shows the longest charge and discharge time, indicating that under the synergistic effect of sulfur doping and oxygen vacancies, it shows the highest specific capacitance. After calculation, the S-NiMn-LDH-Ov prepared in Example 1 and Comparative Examples 1-3 0.5 The specific capacitances of NiMn-LDH@NF, S-NiMn-LDH@NF and NiMn-LDH-Ov@NF are 1903.47 F / g, 983.00 F / g, 1110.13 F / g and 1636.00 F / g, respectively.

[0092] See also Fig.12 From the electrochemical impedance spectra of the electrode materials prepared in Example 1 and Comparative Examples 1-3, it can be seen that compared with the electrode materials prepared in Comparative Examples 1-3, the NiMn-LDH-Ov prepared in Example 1 0.5 The @NF exhibits a semicircle with the smallest diameter in the low-frequency region and the largest slope in the high-frequency region, indicating its minimum charge transfer resistance and optimal ion diffusion behavior, which is due to the synergistic effect of sulfur doping and oxygen vacancies.

[0093] See also Fig.13 Figures a to c are the electrode materials S-NiMn-LDH-Ov prepared in Example 1. 0.5 Power-law relationship between the peak current and scan rate of @NF, the capacitance contribution at scan rates of 5 to 100 mV / s, and the cycling performance at a current density of 30 A / g.

[0094] In order to further study the charge storage mode of the electrode material, the CV curve was fitted according to the following formulas (1) and (2) to analyze its capacitance behavior:

[0095]

[0096] in, i represents the current density, v is the scan rate, a is a constant, and b is a calculated value between 0.5 and 1. Whereas a b value of 0.5 indicates a diffusion-controlled process, a b value of 1 indicates a capacitive non-Faraday type charge storage mechanism. Fig.13 a is the electrode material S-NiMn-LDH-Ov prepared in Example 1 0.5 The peak current of @NF has a power law relationship with the scan rate. The b values ​​calculated based on the anodic peak and the cathodic peak are 0.61 and 0.66, respectively, indicating that the contribution of diffusion control is dominant. 0.5 @NF capacitance contribution at scan rates of 5 to 100 mV / s. It can be seen that the diffusion-controlled proportion is 90.6% at a scan rate of 5 mV / s, showing typical pseudocapacitive performance. Even at a scan rate of 100 mV / s, the diffusion-controlled capacitance proportion is still 70.4%, indicating that S-NiMn-LDH-Ov 0.5 @NF has excellent pseudocapacitive performance and rate performance. Figure c shows the cycle performance at a current density of 30 A / g. After 10,000 charge and discharge cycles, there is still a coulombic efficiency of nearly 100% and a capacitance retention rate of 92.89%. The charge and discharge curves of the first 10 cycles and the last 10 cycles are basically the same, showing that S-NiMn-LDH-Ov 0.5 @NF Excellent cycling stability.

[0097] In summary, the present invention provides a sulfur-doped nickel-manganese layered double hydroxide electrode material, a preparation method and a capacitor. By growing nickel-manganese layered double hydroxide on a three-dimensional nickel foam, combined with the synergistic effect of sulfur doping and oxygen vacancies, the conductivity and electron transfer efficiency of the electrode material are improved, thereby improving the actual specific capacitance, rate performance and cycle stability of the supercapacitor, making it have better electrochemical properties, and promoting the development of transition metal layered double hydroxides in the field of supercapacitors.

[0098] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.

Claims

1. A method for preparing a sulfur-doped nickel-manganese layered double hydroxide electrode material, characterized in that: include: S1: dissolving a metal salt, hexamethylenetetramine and thioacetamide in water to obtain a mixed solution; wherein the metal salt is a nickel salt and a manganese salt; wherein in the mixed solution, the molar ratio of the nickel salt, the manganese salt and the hexamethylenetetramine is (2-4):1:(1.25-2.5), and the concentration of the metal salt is 0.03-0.1 mol / L; and the molar ratio of the thioacetamide to the metal salt is (0.05-0.1):1; S2: immersing the nickel foam in the mixed solution to perform a hydrothermal reaction, and after the reaction is completed, washing and drying to obtain a nickel foam with sulfur-doped nickel-manganese layered double hydroxide; S3: immersing the nickel foam on which sulfur-doped nickel-manganese layered double hydroxide is grown in a sodium borohydride aqueous solution for reaction, and after the reaction is completed, washing and drying are performed to obtain a sulfur-doped nickel-manganese layered double hydroxide electrode material; the concentration of the sodium borohydride aqueous solution is 0.3-1 mol / L.

2. The method for preparing the sulfur-doped nickel-manganese layered double hydroxide electrode material according to claim 1, characterized in that: The nickel salt is nickel chloride hydrate, nickel nitrate hydrate or nickel sulfate hydrate.

3. The method for preparing the sulfur-doped nickel-manganese layered double hydroxide electrode material according to claim 1, characterized in that: The manganese salt is manganese chloride hydrate, manganese nitrate hydrate or manganese sulfate hydrate.

4. The method for preparing the sulfur-doped nickel-manganese layered double hydroxide electrode material according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 100° C. to 180° C., and the reaction time is 10 to 16 hours.

5. The method for preparing the sulfur-doped nickel-manganese layered double hydroxide electrode material according to claim 1, characterized in that: In S3, the nickel foam on which the sulfur-doped nickel-manganese layered double hydroxide is grown is immersed in a sodium borohydride aqueous solution, and the reaction temperature is 0° C. to 30° C., and the reaction time is 0.5 to 1.5 h.

6. A sulfur-doped nickel-manganese layered double hydroxide electrode material prepared by the method according to any one of claims 1 to 5, characterized in that: At a current density of 1 A / g, the specific capacitance of the sulfur-doped nickel-manganese layered double hydroxide electrode material is 1110.13-1903.47 F / g.

7. A capacitor, characterized in that: It includes the sulfur-doped nickel-manganese layered double hydroxide electrode material as described in claim 6.

Citation Information

Patent Citations

  • Layered double hydroxide composite electrode material and preparation method and application thereof

    CN109411238A